2001
DOI: 10.1046/j.1365-2141.2001.03073.x
|View full text |Cite
|
Sign up to set email alerts
|

International prognostic scoring system and TP53 mutations are independent prognostic indicators for patients with myelodysplastic syndrome

Abstract: Summary. We applied the International Prognostic Scoring System (IPSS) to our series of 118 patients with myelodysplastic syndrome (MDS) to determine its validity, and also used univariate and multivariate analyses to evaluate the prognostic significance of TP53 configurations. Sixteen patients with the mutation had a strikingly worse prognosis and the multivariate analysis demonstrated that this alteration was the most significant factor. The prognostic comparison between patients with and without the mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 13 publications
1
44
1
2
Order By: Relevance
“…TP53 mutations in 9Á4% of MDS patients in our large single institution study is slightly higher than in previous reports (Jonveaux et al, 1991;Ludwig et al, 1992;Lai et al, 1995), although some reports have shown frequencies around 11-14% (Wattel et al, 1994;Kaneko et al, 1995;Kita-Sasai et al, 2001). The overall higher incidence in our study is possibly due to the sensitive technique, which detected low level clones (<20% mutant allele burden in 8 patients), the inclusion of patients with therapy-related myeloid neoplasms and also sequencing of the whole gene.…”
Section: Discussioncontrasting
confidence: 51%
“…TP53 mutations in 9Á4% of MDS patients in our large single institution study is slightly higher than in previous reports (Jonveaux et al, 1991;Ludwig et al, 1992;Lai et al, 1995), although some reports have shown frequencies around 11-14% (Wattel et al, 1994;Kaneko et al, 1995;Kita-Sasai et al, 2001). The overall higher incidence in our study is possibly due to the sensitive technique, which detected low level clones (<20% mutant allele burden in 8 patients), the inclusion of patients with therapy-related myeloid neoplasms and also sequencing of the whole gene.…”
Section: Discussioncontrasting
confidence: 51%
“…TP53 mutations are exceedingly rare in the 5q-syndrome, 13 however, they frequently occur in MDS with complex karyotypes including del(5q) or in therapyrelated MDS, invariably implying a poor outcome, 14,15 The frequency of small fractions of BM progenitors with abnormal p53 expression, which may fall below the detection threshold for a mutational analysis, is unknown in MDS with isolated del(5q).…”
Section: Mutated Tp53 Pre-treatmentmentioning
confidence: 99%
“…5,6 In particular, TP53 mutations have been shown to confer resistance to lenalidomide in MDS with del(5q).…”
mentioning
confidence: 99%